What Do You Know About Fat? - Jennifer Hillan; Claudia Peñuela (EDIS, 2011)
We hear a lot about fat: in the news, from friends, and in the books and magazines we read. For help sorting out all the information about fat, read this revised 3-page fact sheet written by Jennifer Hillan and Claudia Peñuela, and published by the UF Department of Family, Youth and Community Sciences, September 2011.